2013
DOI: 10.18097/pbmc20135906673
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic preconditioning modifies the activity of prond antioxidant systems in rat hippocampus

Abstract: The effects of repetitive mild hypobaric hypoxic preconditioning upon pro- and antioxidant systems in rat hippocampus were studied. It was found that three-trial preconditioning by mild hypobaric hypoxia (360 mm Hg, 2 h) induced moderate oxidative stress immediately after the last preconditioning trial. In addition, it down-regualted the levels of peptide antioxidants (Trx-1, Trx-2, Cu,Zn-SOD) and several lipid peroxidation products 24 h later.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
(26 reference statements)
0
2
1
Order By: Relevance
“…Our study confirmed it: ischemia in the preconditioned animals was not accompanied by any signs of oxidative stress, nor was there any pronounced activation of ROS-induced processes as observed in the control animals with Ischemia. The application of compounds with an antioxidant activity in the CPreC protocol may lead to the weakening of the cytoprotective effect induced by preconditioning due to the inhibition of ROS, which play a signaling role in the mechanism of organism adapting to hypoxia (Kislin et al 2013). In our study, this was not observed.…”
Section: Resultscontrasting
confidence: 53%
See 1 more Smart Citation
“…Our study confirmed it: ischemia in the preconditioned animals was not accompanied by any signs of oxidative stress, nor was there any pronounced activation of ROS-induced processes as observed in the control animals with Ischemia. The application of compounds with an antioxidant activity in the CPreC protocol may lead to the weakening of the cytoprotective effect induced by preconditioning due to the inhibition of ROS, which play a signaling role in the mechanism of organism adapting to hypoxia (Kislin et al 2013). In our study, this was not observed.…”
Section: Resultscontrasting
confidence: 53%
“…This may be due to the time interval taken to evaluate the ROS-induced processes. For example, in Kislin et al (2013), it was shown that immediately after hypoxic PreC in the brain tissue, there was an activation of free radical reactions, but 3 hrs and 24 hrs later, on the contrary, they were inhibited, resulting in a decrease in SOD expression.…”
Section: Resultsmentioning
confidence: 99%
“…It was noted that in the hippocampus and cerebellum, the proportion of necrotic neurons is significantly higher than in other cerebral structures. Histochemical studies of localization of free radical oxidation (FRO) products in the brain of animals, which had cardiac arrest, showed that neurons of selectively vulnerable hippocampal areas are primal targets for FRO in the brain during reperfusion [1].…”
Section: Introductionmentioning
confidence: 99%